A Qualitative Exploration of UK Leisure Horse Owners’ Perceptions of Equine Wellbeing - Rebecca Smith; Tamzin Furtado; Charlotte Brigden; Gina Pinchbeck; Elizabeth Perkins (Animals, 2022)
Human assessment of equine wellbeing is fundamental to ensuring the optimal care of domestic horses. However, terminology associated with wellbeing is still not fully defined and there are currently no validated quality of life (QoL) assessment tools. Furthermore, little is known about what equine wellbeing or QoL means to horse owners, or how their beliefs impact on the management decisions they make for their horse. This study sought to establish how UK leisure horse owners use wellbeing-related terminology by exploring their accounts within a focus group setting. Four online focus group discussions (FGD) were held and qualitative data were collected. FGDs involved a semi-structured discussion, followed by a group activity to compare seven equine wellbeing-related terms of interest introduced by the facilitator. The collected data were analysed using a constructivist grounded theory approach, and also by content analysis, to examine the frequency and subjective meaning of the terms of interest. The results showed that horse owners did not clearly delineate between different terms, rather, they used the terms in the context of their own assessments of their horse. The meanings assigned to what owners experienced with their horse were individual and subjective, shaped by past experiences, relationships with their animal, and peers or social groups. This individualised construction of equine wellbeing impacted on the meaning conveyed when using wellbeing-related terminology. In this study, we extend the literature on equine wellbeing terminology usage, and highlight differences between the academic literature and the real-world experiences of horse owners.